La genèse de la Françafrique, des indépendances à 1982 - Catherine Coquery-Vidrovitch (Cahiers d’histoire)
Did Independence changed from colonial to neocolonial times ? In Francophone Africa the labour code appeared in 1952, universal voting in 1956. EU (1957) accepted to receive African French and Belgium colonies. With new rules, CEE/ACP agreements (Africa – Caribbean islands– Pacific), the purpose remained similarly complementary and contradictory. CCCE became CCCE (Central Centre of Economic Cooperation), and CFA franc became the same (African Financial Community Franc). Infrastructure equipment remained more and more insufficient, and public debt more and more important. A dramatic cycle of debt and loans progressed. Thence Françafrique emerged, directly controlled by President Charles De Gaulle with his “Mister Africa”, Jacques Foccart. This is the topic of this paper.